1993
DOI: 10.1163/22941932-90001326
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Acacia Mangium Grown in Malaysia

Abstract: A study on the tissue proportions and fibre dimensions of plantation-grown Acacia mangium was carried out. Ten selected trees from two age groups (4- and 8-year-old) were obtained from plantation forests in Selangor. Disks were taken from four sampling heights. Acacia mangium wood is diffuse-porous with mostly solitary vessels. The rays are uniseriate. The average percentage of fibres, vessels and rays of 4-year-old and 8-year-old samples are 85.8%, 9.1%, 5.2% and 84.8%, 9.8%, 5.3%, respectively. Acacia is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 1 publication
3
12
0
Order By: Relevance
“…Sahri et al (1993) found the same axial variation in Acacia mangium with a fi ber length decrease with height (1.026 mm to 0.849 mm). Eucalyptus globulus shows the same axial variation of wood fi ber length.…”
Section: Tavares F Et Alsupporting
confidence: 54%
See 3 more Smart Citations
“…Sahri et al (1993) found the same axial variation in Acacia mangium with a fi ber length decrease with height (1.026 mm to 0.849 mm). Eucalyptus globulus shows the same axial variation of wood fi ber length.…”
Section: Tavares F Et Alsupporting
confidence: 54%
“…Sahri et al (1993), in 4-and 8-year-old trees of Acacia mangium registered the same trend of radial variation as well as Honjo et al (2005) for ages of 2 to 14 years where the fi ber length varied between 0.9 mm and 1.3 mm near the bark and between 0.4 mm and 0.6 mm near the pith. The same pattern of fi ber length variation was reported for Acacia bilimeki (1.032 mm to 1.077 mm) and it was different in Acacia cochiacantha with 0.780 mm near the pith and 0.727 mm close to the bark (QUINTANAR ISAIAS et al, 2005).…”
Section: Tavares F Et Alsupporting
confidence: 52%
See 2 more Smart Citations
“…The wood can be used for solid wood products (Griffin et al, 2011) in building and carpentry (Jablonski et al, 2010), panel products, pulp and paper (Santos el al., 2006(Santos el al., , 2012Anjos et al, 2011;Pereira et al, 2016) and food, fodder, poles and domestic fuelwood (Griffin et al, 2011). The anatomic characteristics are important for all applications, but there are not many reports on the wood anatomy of A. melanoxylon and on its variability (Iqbal, 1983;Sahri et al, 1993;Wilkins and Papassotiriou et al, 1989;Rodrigues et al, 2007;Tavares et al, 2011). The A. melanoxylon wood shows distinct growth rings with dense latewood bands, solitary or radial grouped vessels, vessel diameter between 100-300 m, low percentage of paratracheal parenchyma, homogeneous 1-3-seriate rays up to 40 cells high (Dadswell & Eckersley 1935;Wilkins and Papassotiriou et al, 1989).…”
Section: Palavras-clavementioning
confidence: 99%